New Body, new me?: fat women characters in North American fiction, 1976-2013 - Green, Michelle (2019)
“New Body, New Me? Fat Women Characters in North American Fiction, 1976-2013” unveils the cultural and literary significance of fictional journeys of fat women characters since the emergence of the fat-acceptance movement in the late 1960s. In doing so, it examines the role of fiction in imagining new possibilities and cultural imaginaries of gender and size. By examining novels that range from bestselling popular fictions, to niche fictions that are becoming popular with the fat-acceptance community, the thesis reassesses the familiar topics of consumption and weight loss in fat depictions through the lens of genre and narrative journeys. An analysis of Margaret Atwood’s Lady Oracle (1976), Wally Lamb’s She’s Come Undone (1992), Susan Stinson’s Venus of Chalk (2004) and Lionel Shriver’s Big Brother (2013) reveals how fat women have been imagined in a variety of transformational weight loss and size acceptance journeys framed around maturity, recovery, community and family. The types of journeys in which women are imagined speak to collective assumptions about gender and size in the second half of the twentieth century and the beginning of the twenty-first and reveal how fat women’s bodily and psychological journeys share several conventions including painful pasts, trials of gender and sexual visibility, difficult and convoluted paths to self-expression, and a divided sense of self. Moreover, these representative fictions of fatness reveal how fat representations are characterised by persistent and creative attempts to undermine myths of transformational change and total self-control. The significance of weight loss and size acceptance to representations of fatness in this period has hitherto been neglected, but by mapping the trend of narrative journeys, this project works to illuminate the full extent to which transformation has been central to satirical, painful, or triumphant depictions of fat women’s contested subject hood.